Reactivity of CO and C2H4 on Bimetallic PtxAg1‐x/Pt(111) Surface Alloys Investigated by High‐Resolution X‐ray Photoelectron Spectroscopy. Issue 12 (8th June 2018) - Bauer, U.; Späth, F.; Düll, F.; Bachmann, P.; Steinhauer, J.; Steinrück, H.‐P.; Papp, C.
Abstract: The front cover artwork is provided by the group of Dr. Christian Papp at the chair of Prof. Hans‐Peter Steinrück. The image shows the two metals platinum and silver that form a bimetallic surface alloy in the first layer. On this model catalyst, depending on the relative Ag content, the adsorption strength of CO can be enhanced and C−H bond activation (e.g. for C2 H4 production) is achieved much easier as deduced from the diagrams on top. Read the full text of the Article at10.1002/cphc.201800044 . Abstract : "The adsorption and thermal reactivity of CO and C2 H4 on well‐defined bimetallic Ptx Ag1‐x /Pt(111) surface alloys (with x =0.67, 0.50, 0.38 and 0.32) is investigated by using in situ synchrotron‐based high‐resolution X‐ray photoelectron spectroscopy…" This and more about the story behind the front cover can be found in the Article at10.1002/cphc.201800044 .